2008
DOI: 10.1074/jbc.m805400200
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 Modulates Cell Proliferation through the MAPK/ERK Pathway during Erythropoiesis and Has No Effect on Heme Biosynthesis

Abstract: UCP2, an inner membrane mitochondrial protein, has been implicated in bioenergetics and reactive oxygen species (ROS) modulation. High levels of UCP2 mRNA were recently found in erythroid cells where UCP2 is hypothesized to function as a facilitator of heme synthesis and iron metabolism by reducing ROS production. We examined UCP2 protein expression and role in mice erythropoiesis in vivo. UCP2 was mainly expressed at early stages of erythroid maturation when cells are not fully committed in heme synthesis. Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Previously, we and other research groups have reported that UCP2 is expressed in haematopoietic and human pluripotent stem cells [15], [19], [20]. To confirm the common expression of UCP2 in stem cells, we now tested the protein abundance in mESCs.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we and other research groups have reported that UCP2 is expressed in haematopoietic and human pluripotent stem cells [15], [19], [20]. To confirm the common expression of UCP2 in stem cells, we now tested the protein abundance in mESCs.…”
Section: Resultsmentioning
confidence: 99%
“…As ABC-meÀ/À erythroid cells show an increase in mitochondrial superoxide, a superoxide dismutase 2 (SOD2) mimetic compound (MnTBAP) was used to reduce mitochondrial superoxide levels. 17 Isolated blood cells from day 10.5 pc embryos were differentiated in a hematopoietic semi-solid media (see Materials and Methods). The number of the (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Samples were obtained after differentiation of these colonies and apoptosis was analyzed using flow cytometry (TUNEL-BrdU, as described below for embryonic blood) and also for hemoglobin content by measuring absorbance (after lysis of colonies) as previously described. 6,17 Fluorescence-activated cell sorting (FACS) analysis. Isolated embryonic blood from day 10.5 pc (B1 Â 10 5 ) was immunostained simultaneously with PE-conjugated anti-TER119 (1 : 100) (BD Pharmingen, San Diego, CA, USA) and FITC-conjugated anti-CD71 (Transferrin receptor) (1 : 100; BD Pharmingen).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of UCP2 gene occurs at early stages of erythroid maturation (when cells are not fully committed to heme biosynthesis), and high levels of UCP2 protein were found in erythroid cells. Detailed analysis of bone marrow and fetal liver progenitor cells, in vitro and in vivo , revealed that UCP2 deficiency led to a significant decrease in cell proliferation at the Epo‐dependent phase of erythropoiesis, without affecting heme biosynthesis (112). This is an interesting finding indicating that UCP2 is another regulator of erythropoiesis and suggests that inhibition of UCP2 function may contribute to the development of anemia.…”
Section: Key Regulators Of Erythropoiesis: Iron Homeostasis‐cellular mentioning
confidence: 99%